Pelaksanaan Cek Kesehatan oleh Mahasiswa KKN Universitas Abdurrab di SMK Islam Inayah Ujung Batu: Meningkatkan Kesadaran Kesehatan di Kalangan Siswa - Nadya Putri Auliya Serawaidi; Natasya Amelia Putri; Vionica Elsa Dania Putri; Raudatuz Zahra Faisal (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Health check activities in the school environment are an important effort to increase health awareness among adolescents. KKN students from Abdurrab University carried out health check activities at SMK Islam Inayah on August 30, 2024, which were attended by PMR students with teacher assistance. This activity includes checking blood pressure, weight, height, and education on healthy lifestyles. The results of the activity showed student enthusiasm and support from the school. This activity is expected to be the first step in integrating routine health programs in schools to support student health in a sustainable manner.